2018
DOI: 10.1111/codi.14247
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic colitis: a population‐based case series over a 9‐year period in Northern Ireland

Abstract: Overall, CC and LC are benign conditions with similar demographics, clinical associations, management and outcomes. Separate sampling of the right and left colon is advised at colonoscopy if this diagnosis is being considered, but left colonic sampling, which can be performed at flexible sigmoidoscopy, will diagnose the vast majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 38 publications
(54 reference statements)
2
13
0
Order By: Relevance
“…It is of note that in a considerable percentage of MC cases, a range of endoscopic abnormalities was reported, such as patchy reddening/ inflammation, alteration of the vascular mucosal pattern, mosaic pattern, diffuse mucosal cloudiness, mucosal nodularity or mucosal defects. [9][10][11][12] The etiology of MC remains unsettled.…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that in a considerable percentage of MC cases, a range of endoscopic abnormalities was reported, such as patchy reddening/ inflammation, alteration of the vascular mucosal pattern, mosaic pattern, diffuse mucosal cloudiness, mucosal nodularity or mucosal defects. [9][10][11][12] The etiology of MC remains unsettled.…”
Section: Discussionmentioning
confidence: 99%
“…An overall pooled incidence rate of 11.4 (95% CI: 9.2–13.6, I 2 = 99.72%) cases of MC per 100,000 person‐years was calculated based on studies providing population‐based data 10–31 . Several studies from North America 20 , 27 and Europe 14,16–18,25,26,29 reported variations in incidence rates over a 10‐years‐time period in the same region. They all showed an increasing incidence in the early years, which has reached a plateau 32 .…”
Section: Methodsmentioning
confidence: 99%
“…The pooled incidence rate for CC 10 , 11 , 13–24 , 26–31 , 33–36 was 4.9 (95% CI: 4.2–5.7, I 2 = 98.3%) cases per 100,000 person‐years. The pooled LC incidence rate was 5.0 (95% CI: 4.0–6.1, I 2 98.75%) cases per 100,000 person‐years 10–31 . Geographic variations in the incidence of MC have been reported; however, the limited number of studies from Southern Europe compared to Northern Europe and the lack of direct comparative studies from different countries for the same time period does hinder firm conclusions on this matter.…”
Section: Methodsmentioning
confidence: 99%
“…We recommend that colonoscopy, rather than flexible sigmoidoscopy, be routinely performed if MC is suspected as histologic changes can be patchy in distribution, and inflammatory severity is greatest in the more proximal colon. Flexible sigmoidoscopy, however, can diagnose >90% of MC 29,30. Classic histologic features of LC include >20 intraepithelial lymphocytes per 100 epithelial cells.…”
Section: General Overviewmentioning
confidence: 99%